Storage of supercritical carbon dioxide in nanoporous media - Omer Salim; Keerti Vardhan Sharma; Mohammad Piri (Journal of CO2 Utilization)
This study investigates the adsorption behavior of supercritical carbon dioxide (scCO2) in nanoporous materials, with a particular focus on the effects of temperature and pore size. Using a novel gravimetric method, we examined three samples of mesoporous silica MCM-41 with varying pore diameters of 60, 80, and 100 Å. The pore size distributions for these samples were confirmed by nitrogen sorption analysis, revealing significant uniformity. The adsorption and desorption isotherms of scCO2 were measured experimentally across a temperature range of 304.15–373.15 K (Kelvin). The results showed that the adsorption capacity was increased at lower temperatures, underscoring the inverse relationship between scCO2 density and temperature. A comparison between mesoporous materials and bulk spaces highlighted the superior CO2 storage capacity of the former, owing to their larger surface area and pore volume. Furthermore, the thermodynamic behavior of scCO2 inferred from the adsorption isotherms demonstrated the formation of a denser phase similar to the liquid at conditions above critical temperature and well above critical pressure. The findings from this study significantly improve the current understanding of the phase behavior of scCO2 in confined spaces and offer valuable insights for CO2 storage.